2021
DOI: 10.3390/su13169463
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Review on IoT Threats and Attacks: Taxonomy, Challenges and Solutions

Abstract: The Internet of Things (IoT) plays a vital role in interconnecting physical and virtual objects that are embedded with sensors, software, and other technologies intending to connect and exchange data with devices and systems around the globe over the Internet. With a multitude of features to offer, IoT is a boon to mankind, but just as two sides of a coin, the technology, with its lack of securing information, may result in a big bane. It is estimated that by the year 2030, there will be nearly 25.44 billion I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 205 publications
(124 reference statements)
0
48
0
Order By: Relevance
“…Based on the scenarios from a specific industry and the infrastructure to which IoT is being applied to, the requirements and consequent security measures may be changed or adjusted. Nevertheless, the common security requirements [10][11][12][13] of IoT systems can be summarized as given in Table 2.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the scenarios from a specific industry and the infrastructure to which IoT is being applied to, the requirements and consequent security measures may be changed or adjusted. Nevertheless, the common security requirements [10][11][12][13] of IoT systems can be summarized as given in Table 2.…”
Section: Figurementioning
confidence: 99%
“…In the above sub-section, some empirical based solutions have been listed in Table 2 corresponding to the given threat or attack. Based on the studies performed in [11,[45][46][47], it is observed that some ubiquitous state-of-the-art technologies such as Blockchain, Fog Computing, Edge Computing, SDN, Artificial Intelligence can be used to enhance the security in an IoT environment. These technologies are vital and have enormous potential for addressing the IoT ecosystem's security concerns.…”
Section: State-of-art Iot Security Mitigationsmentioning
confidence: 99%
“…However, such data, typically referred to as synchrophasor data, can be exploited by cyber-attacks such as denial of service (DoS), distributed denial of service (DDoS), false data injection, spoofing, data tampering, etc. [33]. These attacks put the WAMS at risk, and its efficacy becomes questionable.…”
Section: Blockchain Architecture For Spamentioning
confidence: 99%
“…Inside the model, the distributer's undertaking is to gather the information and send data to endorsers through the intercession layer which is the agent. The part of the merchant, then again, is to guarantee security through cross-checking the distributers' and supporters' authorization [35]. MQTT offers three methods of accomplishing this (Service Quality), on account of that the distributer has the likelihood to characterize the nature of its message: (i) QoS0 (At most once): The most un-dependable mode yet in addition the quickest.…”
Section: Message Queuing Telemetry Transport (Mqtt)mentioning
confidence: 99%